Teaching cyber security to non-tech students. (May 2019) - Arora, Bela
The majority of cyber security education and training has been based in computer science departments, but we are now seeing the agenda filtering into the political science and international studies curriculum. There exists a challenge in presenting the topic in a non-technical and engaging way. This article will explore the use of Hydra Minerva environment, commonly used in Police Sciences, to facilitate simulations that bring to life the challenges of incident management while enhancing the employability skills of the students. Hydra Minerva facilities offer an alternative to traditional classroom simulations and computer-assisted scenarios that can be invaluable across the curriculum.